International marketing data and statistics 1983 (London : Euromonitor Publications, 1983)
The handbook presents statistical information on all basic marketing parameters for 132 countries throughout the world. Each set of statistics is presented in a four page comparative tabulation for immediate use and comparison, and there are special sections on consumer spending and households. This publication is widely accepted as one of the most useful sources of statistical documentation and research, it constitutes an invaluable world marketing guide.
Includes index.
rpm 17/08/2018
Loans
Keywords: Statistics; Commercial statistics; Market surveys; Economic history; Marketing international; Marketing; Commerce